2010
DOI: 10.2308/bria.2010.22.2.69
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ingratiation and Client Incentive on Auditor Judgment

Abstract: Anecdotal evidence from practice suggests clients can influence auditor judgment using ingratiation, a strategic influence tactic through which the ingratiator attempts to induce positive affect to facilitate persuasion. I provide initial academic evidence concerning the effect of ingratiation on auditor judgment. I find that when the client ingratiates, auditors are more likely to comply with the requests of clients with low incentive to influence the auditor than those with high incentive. Thus, ingratiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 34 publications
3
33
0
3
Order By: Relevance
“…For example, Tice et al (2007) find that, after an initial act requiring self-control, participants performed equally well on subsequent tasks requiring self-control after receiving inductions of positive mood or emotion as those participants whose self-control resources were not depleted, and better than participants whose self-control resources were depleted but did not receive the intervention. Thus, implementable strategies such as ingratiating techniques (e.g., compliments) can bolster positive affect (Robertson 2010), which in turn should replenish a depleted ego. Beyond directly examining positive affect, research has demonstrated other affectrelated mechanisms that replenish ego.…”
Section: Restoring Self-control Resourcesmentioning
confidence: 99%
“…For example, Tice et al (2007) find that, after an initial act requiring self-control, participants performed equally well on subsequent tasks requiring self-control after receiving inductions of positive mood or emotion as those participants whose self-control resources were not depleted, and better than participants whose self-control resources were depleted but did not receive the intervention. Thus, implementable strategies such as ingratiating techniques (e.g., compliments) can bolster positive affect (Robertson 2010), which in turn should replenish a depleted ego. Beyond directly examining positive affect, research has demonstrated other affectrelated mechanisms that replenish ego.…”
Section: Restoring Self-control Resourcesmentioning
confidence: 99%
“…However, prior studies of accounting professionals in other cultures have concluded that both time budget pressure and client pressure increase auditor propensity to make unethical decisions(Robertson, 2010). While the time pressure conditions were adopted from a prior study, the high time pressure manipulation indicated that, owing to reduced audit fees, the audit partner decided to reduce budgeted hours.…”
mentioning
confidence: 99%
“…But there are some evidences that clients may inluence auditor judgment through ingratiation which can inluence the judgment of the target in many setings [37]. Prior research stated that afect toward the client can inluence auditor judgment; as an example, inexperienced auditors who felt negative afect toward the client assess a higher risk of inventory obsolescence than who did not experience afect toward the client.…”
Section: Auditor's Judgment and Decision-makingmentioning
confidence: 99%
“…Auditors are required to exercise professional skepticism when making judgments based on audit evidence without being inluenced by clients [37,38]. But there are some evidences that clients may inluence auditor judgment through ingratiation which can inluence the judgment of the target in many setings [37].…”
Section: Auditor's Judgment and Decision-makingmentioning
confidence: 99%